2019
DOI: 10.1186/s12884-019-2594-y
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression and associated factors among mothers who gave birth in the last twelve months in Ankesha district, Awi zone, North West Ethiopia

Abstract: BackgroundPostpartum depression is the most common complication of childbearing age women and is a considerable public health problem. The transition into motherhood is a difficult period that involves significant changes in the psychological, social and physiological aspects, and has increased vulnerability for the development of mental illness. More than 1 in 10 pregnant women and 1 in 20 postnatal women in Ethiopia suffer from undetected depression.MethodsCommunity based cross sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
63
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 23 publications
12
63
5
4
Order By: Relevance
“…Items marked with an asterisk (*) are reverse scored (i.e., 3, 2, 1, and 0), and total score is a summation of the 10 item responses. EPDS is structured into four severity ranges: 1) None or minimal depression (0-6), 2) Mild depression (7-13), 3) Moderate depression (14-19), 4) Severe depression (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and a need to refer or follow up suicidal risk.…”
Section: The Edinburgh Postpartum Depression Scale (Epds)mentioning
confidence: 99%
See 2 more Smart Citations
“…Items marked with an asterisk (*) are reverse scored (i.e., 3, 2, 1, and 0), and total score is a summation of the 10 item responses. EPDS is structured into four severity ranges: 1) None or minimal depression (0-6), 2) Mild depression (7-13), 3) Moderate depression (14-19), 4) Severe depression (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and a need to refer or follow up suicidal risk.…”
Section: The Edinburgh Postpartum Depression Scale (Epds)mentioning
confidence: 99%
“…The EPDS has been validated in different cultures showing its importance in mitigating long lasting effects for mothers, their children and society at large (21). It has been widely tested globally including countries in Sub-Saharan Africa (SSA) (22,23).…”
Section: The Edinburgh Postpartum Depression Scale (Epds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review and meta-analysis study in India which assessed 38 studies reported a pooled prevalence of postpartum depression to be 22% (10). Moreover, other individual studies reported earlier showed that postpartum depression was 17.6% in Portugal (11), 27.3% in China(12), 61.4% in Korea(13), 18.6% in Qatar(14), 34.8% in Iraq(15), 34% in Jamaica(16) ,15.4% in Turkey (17), 13.5% and 10.3% in Oman(18), 31.7% in South Africa (19), and 43% in Uganda (20).In Ethiopia, the prevalence of postpartum depression varies between 12.2-33.8% (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…Poor social support (37), poverty (38), and childbirth without the presence of relatives (39), history of depression (40), and poor woman autonomy (41) from socio-demographic variables, multi-parity (42), prime-parity (43,44), multiple children at home (45), negative attitude toward to one's pregnancy (22,(46)(47)(48)(49), depression during pregnancy (42,50), premarital pregnancy (51,52), miscarriage (53), and prenatal high anxiety(47) from pregnancy and newborn related factors, alcohol use in the husband (54), intimate partner violence (22,55,56), poor husbands education (45), husbands unemployment (46,57), and psychiatric problems in the husband (58) among husband related factors were among the associated factors for the development of postpartum depression. In the context of Ethiopia too, poor marital relation (27,29,32,34,35,59), unplanned pregnancy (21,22,24,27,29,32,34), previous history of depression (21,27,28,34), domestic violence…”
Section: Introductionmentioning
confidence: 99%